Identifikasi Permasalahan Metode Pembelajaran IPAS pada Siswa Kelas IV SDN 060866 - Ridha Uli Utami Margolang; Meyliana Perwita Saragih; Arin Huwaida; Syahrial Syahrial (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify the problems of learning methods of Natural and Social Sciences (IPAS) in grade IV students of SDN 060866. The results showed that conventional teacher-centered learning methods were still dominant, causing low student interest and learning outcomes. Most students have not reached the Minimum Completion Criteria (KKM) with a percentage of completeness of only 25%. Teachers face obstacles such as lack of student interest, a less conducive learning environment, and limitations in applying innovative learning methods. To overcome this, teachers plan to implement project-based learning methods that are more interactive and relevant to students' daily lives. This study concludes that more varied and student-centered learning strategies are needed to improve students' motivation and learning outcomes.